Antarctic subglacial lake discharges - Pattyn, Frank (2010)
Antarctic subglacial lakes were long time supposed to be relatively closed and stable environments with long residence times and slow circulations. This view has recently been challenged with evidence of active subglacial lake discharge underneath the Antarctic ice sheet. Satellite altimetry observations witnessed rapid changes in surface elevation across subglacial lakes over periods ranging from several months to more than a year, which were interpreted as subglacial lake discharge and subsequent lake filling, and which seem to be a common and widespread feature. Such discharges are comparable to jökulhlaups and can be modeled that way using the Nye-Röthlisberger theory. Considering the ice at the base of the ice sheet at pressure melting point, subglacial conduits are sustainable over periods of more than a year and over distances of several hundreds of kilometers. Coupling of an ice sheet model to a subglacial lake system demonstrated that small changes in surface slope are sufficient to start and sustain episodic subglacial drainage events on decadal time scales. Therefore, lake discharge may well be a common feature of the subglacial hydrological system, influencing the behavior of large ice sheets, especially when subglacial lakes are perched at or near the onset of large outlet glaciers and ice streams. While most of the observed discharge events are relatively small (101-102 m3 s -1), evidence for larger subglacial discharges is found in ice free areas bordering Antarctica, and witnessing subglacial floods of more than 106 m3 s-1 that occurred during the middle Miocene. Copyright © 2010 by the American Geophysical Union. SCOPUS: ar.k info:eu-repo/semantics/published in "Antarctic Subglacial Aquatic Environments" Geophysical Monograph Series, AGU